Fotogrametri Pemetaan wilayah Untuk Program Studi Arsitektur Fakultas Teknik Universitas Sebelas Maret Surakarta Sebagai Dasar Desain Pengembangan Wilayah - Hanantomo, Roos; Wiryawan Yudhanto, Bramasto (Redtech Putra Benua, 2024)
Regional Mapping Photogrammetry for the Architecture Study Program, Faculty of Engineering, Sebelas Maret University, Surakarta as a basis for regional development design aims to obtain clearer digital image results in mapping an area or land in the form of a file with the extension (.tiff) which can be used for subsequent processes. Carrying out this practical work is deemed necessary because clearer digital images will make it very easy to analyze an area or land in the process of planning regional or land design. Research methods are used to collect data and analyze data. The research methods used are observation, interviews and literature study methods. Based on the author's experience above, regional mapping has been carried out using aerial methods using aerial photogrammetry techniques which produce mapping in the form of clear digital images of an area or land